Researcher of Syntax and Methodology of the Uzbek Language - Sevara Makhmudova (Genius Journals, 2023)
This article analyzes the scientific activity of the Uzbek linguist Irisali Toshaliev, who contributed to the study of the syntax and style of the Uzbek language.
Keywords: syntax; stylistics; articulation; insertion constructions